Reconstruction of the paleo-marine environment during the Ediacaran-Cambrian transition: new insights from geochemical proxies, northern Tarim Platform, Northwest China - Fan, Qi; Fan, Tailiang; Zhu, Zhenyu; Li, Qingping (Frontiers in Earth Science, 2024)
The Cambrian Terreneuvian Yuertusi Formation of the Tarim Basin, regarded as a potential hydrocarbon source rock (TOCmax=29.8 wt%), preserves the record of the Ediacaran to Cambrian Series 2 transition. This study presents a high-resolution multi-proxy investigation of the Sugaitebulake and Yutixi sections of the NW Tarim Basin. Evidence of hydrothermal activity and euxinic conditions in the earliest Cambrian has been delineated by samples from the lower part of the Yuertusi Formation group A, featured by weakly positive Ce anomalies (Ce/Ce*avg.=0.46), extremely positive Eu anomalies (Eu/Eu*avg.=26.39), Y/Ho ratios (Y/Hoavg.=40.48) and several barite layers. Mo and U covariation suggests that the Yuertusi Formation group A and Xiaoerbulake Formation were deposited under sulfidic conditions, whereas the Ediacaran Qigebulake Formation, and Yuertusi Formation groups B and C and D accumulated under suboxic to anoxic conditions. The basin has been weakly restricted and characterized by elevated productivity (Ba-excessavg.=6410.42 ppm) during Terreneuvian time. Suboxic conditions in late Ediacaran time (Qigebulake Formation) became euxinic conditions in association with increased sea level and productivity sustained by hydrothermal activity and upwelling, which have been preserved in the organic-rich lower part of the Yuertusi Formation. Suboxic conditions were reestablished during the Cambrian Terreneuvian time as reflected in the geochemistry of the upper part of the Yuertusi Formation. Euxinic conditions were once again established early in Cambrian Series 2 Xiaoerbulake Formation. Euxinic conditions were coincident with transgressions of the South Tianshan Ocean during that interval. The accumulation and preservation of organic matter of the Early Cambrian northern Tarim Platform reflect the interaction of hydrothermal activity, coastal upwelling, and sea level change.